Human skeletal muscle fibre contractile properties and proteomic profile: adaptations to 3 weeks of unilateral lower limb suspension and active recovery. (15th December 2015) - Brocca, Lorenza; Longa, Emanuela; Cannavino, Jessica; Seynnes, Olivier; de Vito, Giuseppe; McPhee, Jamie; Narici, Marco; Pellegrino, Maria Antonietta; Bottinelli, Roberto
Abstract : Key points: It is generally assumed that muscle fibres go through atrophy following disuse with a loss of specific force and an increase in unloaded shortening velocity. However, the underlying mechanisms remain to be clarified. Most studies have focused on events taking place during the development of disuse, whereas the subsequent recovery phase, which is equally important, has received little attention. Our findings support the hypotheses that the specific force of muscle fibres decreased following unilateral lower limb suspension (ULLS) and returned to normal after 3 weeks of active recovery as a result of a loss and recovery of myosin and actin content. Furthermore, muscle fibres went through extensive qualitative changes in muscle protein pattern following ULLS, and these were reversed by active recovery. Resistance training was very effective in restoring both muscle mass and qualitative muscle changes, indicating that long‐term ULLS did not prevent the positive effect of exercise on human muscle. Abstract: Following disuse, muscle fibre function goes through adaptations such as a loss of specific force ( P O /CSA) and an increase in unloaded shortening velocity, which could be a result of both quantitative changes (i.e. atrophy) and qualitative changes in protein pattern. The underlying mechanisms remain to be clarified. In addition, little is known about the recovery of muscle mass and strength following disuse. In the present study, we report an extensive dataset describing, in detail, the functional and protein content adaptations of skeletal muscle in response to both disuse and re‐training. Eight young healthy subjects were subjected to 3 weeks of unilateral lower limb suspension (ULLS), a widely used human model of disuse skeletal muscle atrophy. Needle biopsies samples were taken from the vastus lateralis muscle Pre‐ULLS, Post‐ULLS and after 3 weeks of recovery during which heavy resistance training was performed. After disuse, cross‐sectional area (CSA), P O /CSA and myosin concentration (MC) decreased in both type 1 and 2A skinned muscle fibres. After recovery, CSA and MC returned to levels comparable to those observed before disuse, whereas Po/CSA and unloaded shortening velocity reached a higher level. Myosin heavy chain isoform composition of muscle samples did not differ among the experimental groups. To study the mechanisms underlying such adaptations, a two‐dimensional proteomic analysis was performed. ULLS induced a reduction of myofibrillar, metabolic (glycolytic and oxidative) and anti‐oxidant defence system protein content. Resistance training was very effective in counteracting ULLS‐induced alterations, indicating that long‐term ULLS did not prevent the positive effect of exercise on human muscle. Key points: It is generally assumed that muscle fibres go through atrophy following disuse with a loss of specific force and an increase in unloaded shortening velocity. However, the underlying mechanisms remain to be clarified. Most studies have focused on events taking place during the development of disuse, whereas the subsequent recovery phase, which is equally important, has received little attention. Our findings support the hypotheses that the specific force of muscle fibres decreased following unilateral lower limb suspension (ULLS) and returned to normal after 3 weeks of active recovery as a result of a loss and recovery of myosin and actin content. Furthermore, muscle fibres went through extensive qualitative changes in muscle protein pattern following ULLS, and these were reversed by active recovery. Resistance training was very effective in restoring both muscle mass and qualitative muscle changes, indicating that long‐term ULLS did not prevent the positive effect of exercise on human muscle.